Characterization and mechanism elucidation of high-quality bio-oil production from co-pyrolysis of waste low-rank coal fines and de-oiled microalgae biomass using bimetallic (Cu-Cr) ZSM-5 catalyst - Rawat S.; Singh A.K.; Chakraborty J.P.; Kumar S. (My University, 2025)
The present study provides a cleaner co-pyrolysis strategy for high-quality bio-oil production by utilizing low-cost residues such as low-rank coal (CL), de-oiled microalgae (ALG), and their blends (CLALG). The heavy metal-loaded Cu-Cr-ZSM-5 catalyst is synthesized by using ion-exchange method and investigated in the CL, ALG and CLALG pyrolysis bio-oil upgradation at different catalyst feed ratios (0.5:1, 1:1, 2:1). The synthesized catalyst was characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and brunauer-emmett-teller (BET) analysis. The synthesized catalyst is nano-crystalline of average size 7 nm. The microstructure of the synthesized catalyst shows stacked nanorods packing with connected intercrystal and intracrystal mesopores. The catalytic and non-catalytic pyrolysis of CL, ALG and CLALG are performed at 600 °C, 10 °C/min for 60 min. The non-catalytic ALG pyrolysis has shown maximum bio-oil yield (35.7%). The synergistic effect of nanorod morphology, active acid sites and excess mesoporosity of catalyst facilitates efficient deoxygenation, denitrogenation and aromatization of pyrolysis bio-oil with oxygen content from 2.1⎼3.1%, nitrogen content 3.5⎼5.1% and aromatic content 49.4⎼54.4% at catalyst feed ratio of 1:1. The maximum obtained higher heating value (HHV) of bio-oil from catalytic pyrolysis of CL (40.1 MJ/kg) followed by CLALG (38.6 MJ/kg) and ALG (36.5 MJ/kg) is very close to diesel oil with HHV (42⎼46 MJ/kg). Further, a co-pyrolysis mechanism is proposed to systematically investigate possible catalytic action sites to yield high-quality bio-oil. Thus, outcomes of the present study enrich information regarding catalyst development, catalyst feed interaction, and thermocatalytic cracking as emerging efforts towards industrial-scale upgradation of bio-oil to engine fuels. © 2024 Elsevier Ltd